Idiotype positive T cells visualized by autoradiography and electron microscopy. - Binz, H (1975)
Anti-idiotypic antibodies were prepared in (CBA X C57BL/6)F1 hybrid mice by immunization either with CBA anti-C57BL/6 alloantiserum or with purified CBA thymus-processed lymphoid cells (T cells) Iodinated anti-mouse Ig or triple sandwich ferritin-labeling techniques served to visualize the reaction between idiotype and anti-idiotype. From 5 to 10% of purified CBA T cells appeared to carry receptors for C57BL/6 antigens. Heavily labeled cells had the morphology of small lymphocytes.